Pakistan, Rushdie and Shame : (A Reading from the Perspective of New Historicism) - Adhikary, Ramesh Prasad (Academia Research Journal, 2023)
The objective of this research paper is to investigate the fragments of historical reality regarding the military coup in Pakistan. In Salman Rushdie's novel Shame, the concept of shame refers to the national shame caused by an attack on democracy. From the standpoint of New Historicism, the work contains several traces and pieces of history relating to the military takeover during Bhutto's government in Pakistan. In Rushdie's Shame, physical details and cruel and horrible acts cover numerous historical truths. Suffiya is a representation of the shame she experienced. She first expresses the shame through her normally ashamed expression. Later, the internal guilt manifests as disease. She keeps feeling more and more ashamed. In this study, a fragment of historical truth about the military coup and the ensuing loss of democracy in Pakistan is indirectly examined beneath the literary specifics of Salman Rushdie's novel Shame. In order to show how Zia's military coup overthrows democracy, the study claims that Rushdie makes many allusions to historical truth that are concealed under fiction and fantasy. The researcher uses the theory of New Historicism, particularly those interpretative tools advanced by Michel Foucault and Stephen Greenblatt, to interpret the text. As part of a qualitative research project, Salman Rushdie’s novel Shame was analyzed using the literary device of new historicism. The study came to the conclusion that Rushdie's Shame uses fiction and fantasy to depict the traces of historical fragments. By fictionalizing official history, it reveals the historical truth that lies behind historical actuality.